Performance analysis of DCT and successive division based digital image watermarking scheme - Prajwalasimha S. N.; Chethan Suputhra .S; Mohan C. S. (Institute of Advanced Engineering and Science, 2019)
In this article, a combined Discrete Cosine Transformation (DCT) and Successive Division based image watermarking scheme is proposed. In many spatial domain approaches, the watermark information is embedded into Least Significant Bits (LSBs) of host image. These LSBs are more vulnerable to noise and other unwanted information contents in the channel, in few cases these are subjected for modifications also. Many frequency domain approaches withstands LSB interference problem but utilizes more execution time. The proposed technique is a frequency domain approach which can withstand LSB attack and utilizes very less execution time than other existing approaches. Performance analysis is done based on robustness, imperceptibility, data embedding capacity and time of execution. The experimental results are better compared to other existing techniques.